PENERAPAN MODEL COOPERATIVE LEARNING TIPE NUMBER HEAD TOGETHER DALAM PEMBELAJARAN PPKN UNTUK MENINGKATKAN PARTISIPASI BELAJAR PESERTA DIDIK : Penelitian Tindakan Kelas Terhadap Peserta Didik Kelas XI IPS 3 SMAN 7 Bandung - Fauzi Nurul Ismi, - (2019)
At present the learning process emphasizes the focus on students, the teacher in the current learning process is only as a facilitator, so the teacher's role is very important in facilitating students to be able to participate in the learning process, so the teacher must be more creative in planning learning because what is found in school there is still a lot of learning that is done as it is, where the learning process that is carried out is only transferring information from the teacher to students, thus making students become passive and less participating. So to overcome these problems applied the Cooperative Learning Models Type Number Head Together in the learning process to increase student learning participation. This study uses a qualitative approach with classroom action research methods, the purpose of classroom action research is to improve and improve the learning process. The stages in this study include planning, action, observation and reflection. Data obtained in this study include teacher observation sheets, and student observation sheets. The results of the observation indicators of student participation in the action of cycle 1 obtained the category "less", in the action of cycle 2 the category "good" and the action of cycle 3 obtained the category "very good". Based on the results of observations it can be concluded that applying Cooperative Learning Models Type Number Head Together in PPKn learning can increase student learning participation.